The Investigation of Pharmacological Activity of Antihistaminic Gels with Dimebon - Mayorova Alena Valentinovna (Journal of Global Pharma Technology, 2017)
The article covers the review of results of investigation for application safety of traditional gel with dimebon and gel with microcapsules dimebon of prolonged anti-allergic action. We have estimated the irritant action is situ and in vivo, studied acute toxicity by the survivability of mice considering calculated LD50. We have determined a signified antihistaminic (anti-oedemic) effect of gels with external application by the reduction of time and intensity of modelled limb swelling of rats. We have established regenerative action of gels by the reduction of burned skin area, augmentation of tissues epithelization and eschar rejection.Keywords: Dimebon, Gel, Anti-allergic action, Antihistaminic, Anti-inflammatory action.